IMPLEMENTATION OF THE PRINCIPLE OF CONSCIOUSNESS AND ACTIVITIES AT THE PHYSICAL EDUCATION LESSONS OF SCHOOL PUPILS (Physical Culture and Sport: Scientific Perspective, 2023)
The article describes the peculiarities of the implementation of the principle of consciousness and activity, which consists, first of all, in ensuring a deep understanding of the purpose of the classes being held, revealing a promising line of improvement, making it an internal need of every student. It is also noted that an important place in the implementation of this didactic principle is the training of students in the conscious management of motor activity. For this, special exercises are used, which help to accurately assess the spatial, temporal and force parameters of movements. They develop in students the ability to consciously analyze their own movements, increase the objectivity of their self-evaluation and improve self-control over the quality of performance of motor actions. The teacher must bring to the student's mind not only what and how to perform, but also why one particular exercise is offered and not another, why it is necessary to observe certain and not other rules for its execution.Any educational process is effective only when it causes and organizes the mental and physical activity of students. That is why the principle of consciousness and activity is designed to activate students in physical education lessons, to relieve them of psychological tension. It should be widely used in physical education. If the teacher ignores this principle or does not know it, then until then the students will not understand and will not want to engage in physical education for the purpose of self-improvement, self-affirmation, and health improvement.Research materials can be used in the educational process of educational institutions when teaching professional sports and methodical disciplines, special seminars for professional training of bachelors of physical culture, for training future specialists for physical culture and health activities; in the process of further development of strategies for the formation of physical culture of students during the period of reforming the educational system of Ukraine.At the same time, the theoretical analysis of scientific research shows that the problem of training future specialists has not yet been sufficiently explored in pedagogical theory, and therefore has not been adequately reflected in the practical activities of educational institutions.
Keywords: principle of consciousness and activity; physical education; pedagogical process; physical education lesson